Analisis Kontribusi Sektor Pertanian Dalam Meningkatkan Produk Domestik Regional Bruto (PDRB) Kabupaten Bener Meriah di Masa Pandemi Covid-19 - Sarah Nur Arifah; Yusrizal Yusrizal; Khairina Tambunan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
The agricultural sector is the largest contributor to the district's GDP. Really Merry. However, this sector has a slow growth rate from year to year. Therefore, this study aims to see how far the contribution of the agricultural sector, especially the agricultural sub-sector, using SS and LQ analysis. This research is qualitative, while the data analysis technique uses Shift Share (SS) and Location Quetient (LQ) analysis. The results showed that the contribution of the agricultural sub-sector to the GRDP of Bener Meriah Regency in 2020 was highest in the Plantation sub-sector, which was 20.39% worth Rp. 741.50 billion of the total GRDP of the agricultural sector in the Bener Meriah area. By using the LQ method, the main agricultural sub-sectors are the horticulture sub-sector, the plantation sub-sector and the food crops sub-sector, while the non-primary agricultural sub-sectors are the livestock and fishery sub-sectors. And based on the analysis of Agricultural Shift Share in Bener Meriah Regency, the fastest growing sub-sectors (PPij > 0) are the horticulture, plantation and fishery sub-sectors with growth values ​​of 3.71% each; 6.57%; and 2.44%. In terms of competitiveness, the agricultural sub-sector with good competitiveness (PPWij > 0) is only the food crops sub-sector with a growth value of 10.65% according to the proportion of the region. Based on the net shift value, no sub-sectors experienced progressive growth (PBij > 0). By comparing the net shift and the competitiveness of the agricultural sub-sector in Bener Meriah Regency, priorities can be established. The priority scales are: 1) food crops sub-sector, 2) fishery sub-sector, 3) livestock sub-sector, 4) horticulture sub-sector, 5) plantation sub-sector. Keywords : Contribution, Location Quotient (LQ), Shift Share (SS), Gross Regional Domestic Product (GRDP)